Shots in the mirror : crime films and society - Rafter, Nicole Hahn, 1939- (Oxford University Press, 2000)
Movies play a central role in shaping our understanding of crime and the world generally, helping us define what is good and bad, desirable and unworthy, lawful and illicit, strong and weak. Crime films raise controversial issues about the distribution of social power and the meanings of deviance, and they provide a safe space for fantasies of rebellion, punishment, and the restoration of order. In this, the first comprehensive study of its kind, well-known criminologist Nicole Rafter examines the relationship between society and crime films from the perspectives of criminal justice, film history and technique, and sociology. Dealing with over 300 films ranging from gangster and cop to trial and prison movies, Shots in the Mirror concentrates on works in the Hollywood tradition but also identifies a darker strain of critical films that portray crime and punishment more bleakly.